Impact of Anti-amyloid-β Monoclonal Antibodies on the Pathology and Clinical Profile of Alzheimer’s Disease: A Focus on Aducanumab and Lecanemab - Shi, Mingchao; Chu, Fengna; Zhu, Feiqi; Zhu, Jie (Frontiers in Aging Neuroscience, 2022)
Alzheimer´s disease (AD) is the most prevalent form of age-related dementia in the world and its main pathological features consist of amyloid-β (Aβ) plaque deposits and neurofibrillary tangles formed by hyperphosphorylated tau protein. So far, only a few AD treatments approved have been applied in clinic, but the effects of these drugs are limited only for partial symptomatic relief to AD patients and are unable to alter AD progression. Afterwards, all efforts for AD treatments with targeting the pathogenic factors were unsuccessful over past decades, which suggested that the parthenogenesis of AD is complex. Recently, disease-modifying therapies (DMTs) that can change the underlying pathophysiology of AD, with anti-Aβ monoclonal antibodies (mabs) (such as aducanumab, bapineuzumab, gantenerumab, solanezumab and lecanemab) have been developed successively and conducted in clinical trials basis on the theory that a systemic failure of cell-mediated Aβ clearance contributes to AD occurrence and progression. In the review, we summarize recent studies on the therapeutic effects and clinical trial results of these mabs in AD patients. Specifically, we focus on discussion of the impact of aducanumab and lecanemab on AD pathology and clinical profiles. The review provides a possible evidence for applying immunotherapy with anti-Aβ mabs in AD and analyzes lessons learnt from these clinical trials in order to further in-depth study the therapeutic and adverse effects of these anti-Aβ mabs on AD.